Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physrevapplied.7.024016
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Hole Transport and Carrier Localization inInAs/InAs1xSbxType-II Superlattice Heterojunction Bipolar Transistors

Abstract: Heterojunction bipolar transistors are used to measure vertical hole transport in narrow-bandgap InAs/InAs 1-x Sb x type-II superlattices (T2SLs). Vertical hole mobilities (µ h) are reported and found to decrease rapidly from 360 cm 2 /V-s at 120 K to ≈ 2 cm 2 /V-s at 30 K, providing evidence that holes are confined to localized states near the T2SL valence miniband edge at low temperatures. Four distinct transport regimes are identified: (1) pure miniband transport, (2) miniband transport degraded by temporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…In region 2, the increase in the mobility with the temperature can be associated with the carriers being set free from the impurity states, with an activation energy of 115 meV. A similar observation has been reported previously in ntype InAs/InAsSb T2SL structures [40], in which results show that above 120 K, the minority carrier hole transport occurs through minibands, while for lower temperatures, the holes are localized and transport is only due to phonon-assisted tunneling.…”
Section: Theoretical Modelsupporting
confidence: 85%
“…In region 2, the increase in the mobility with the temperature can be associated with the carriers being set free from the impurity states, with an activation energy of 115 meV. A similar observation has been reported previously in ntype InAs/InAsSb T2SL structures [40], in which results show that above 120 K, the minority carrier hole transport occurs through minibands, while for lower temperatures, the holes are localized and transport is only due to phonon-assisted tunneling.…”
Section: Theoretical Modelsupporting
confidence: 85%
“…Since the first demonstration of SLSs for infrared (IR) detectors [12], InAs/Ga(In)Sb SLSs continue to improve [19], while InGaAs/InAsSb SLSs [15,20] have also shown promising results. Researchers are currently addressing the poor hole mobility [21] and carrier localization [22,23] effects in n-type SLS to improve the diffusion length. They have also explored p-type SLS detectors, but surface passivation leading to surface leakage current [24,25] remains an insurmountable problem.…”
Section: Introductionmentioning
confidence: 99%
“…With the PL technique, 15 however, the experimental manifestation of the localization sites occurred mainly for T < 60 K, whereas our photocurrent results were obtained for T > 70 K. We suggest that the sensitivity of our photocurrent technique in the higher temperature range is possible because of the lower level of injection (dp % 10 12 cm À3 ) as compared with the elevated level (dp % 10 16 cm À3 ) in the PL technique, keeping the localizations sites far from saturation. In the other investigation, Olson 16 found that the hole mobility exhibits different behavior in four separate temperature intervals. Their interval number 2 (67-110 K) best corresponds to the interval (72-98 K) of our results in Fig.…”
Section: Discussion Of Localizationmentioning
confidence: 92%
“…The first, by Steenbergen et al, 15 used temperature-dependent and excitation-dependent photoluminescence (PL) spectroscopy in MWIR samples to demonstrate the existence of the sites and to measure their energy depth. The second, by Olson et al, 16 used the characteristics of a specially made bipolar heterojunction transistor with a base consisting of LWIR (12.5 lm cutoff) InAs/InAsSb to measure the hole mobility in the growth direction as a function of temperature. The third is the present work, in which we have used the temperature dependence of the photocurrent in MWIR nBn devices to measure the energy depth of the localization sites and demonstrate that they are distributed throughout the absorber volume.…”
Section: Discussion Of Localizationmentioning
confidence: 99%
See 1 more Smart Citation